Sistem Informasi Akuntansi Kas Berbasis Web Pada Bengkel Yuwa Motor - Rezagi Meilano; Heriyani; Hari Zidan Rathomi (Journal of Applied Accounting And Business, 2023)
Bengkel Yuwa Motor is a service company engaged in repair services. Every activity of cash inflow and outflow transactions is recorded into a memorandum and then copied to Spreadsheet. This can have bad consequences such as delays, miscalculations from data processing actors and inaccurate report results due to data sources that take a relatively long time because the amount of data processed is very large. Therefore, this study discusses the creation of a cash inflow and cash out calculation system as a software development method consisting of analysis, design, program code creation and testing. The data collection technique used consisted of observation, interviews and literature study. This cash inflow and outflow information system is expected to assist Yuwa Motor Workshop in processing data relating to cash in and cash out